Successful Management of Massive Obstetric Haemorrhage due to Placenta Previa/Accreta - A Case Report - Chowdhury, S; Rashid, M (Journal of Bangladesh College of Physicians and Surgeons, 2011)
DOI: 10.3329/jbsp.v29i1.7172 J Bangladesh Coll Phys Surg 2011; 29:46-48